2021
DOI: 10.1002/cbin.11709
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐oncogenic PTEN induces ovarian cancer cell senescence by targeting P21

Abstract: Deletion and mutation of phosphatase and tensin homolog deleted on chromosome10 (PTEN) are closely associated with the occurrence of tumors. Tumor suppressor gene PTEN mutation plays an important role in the pathogenesis of ovarian cancer. However, it has been unclear whether it can regulate the senescence of ovarian cancer cells. We speculated that PTEN might inhibit the occurrence and development of ovarian cancer by promoting the expression of P21. We found that the expression of TRIM39 in human ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Somatic PTEN mutations, combined with KRAS mutations, may predispose to invasive and metastatic endometrioid ovarian cancer. Targeted therapies for these mutations in ovarian cancer type I have been unsatisfactory [82,83]. Ovarian cancer risk-reducing surgery is not recommended for PTEN pathogenic variant carriers, but they face an increased risk of endometrial cancer (approximately 5-10%) [76].…”
Section: Pten-the Phosphatase and Tensin Homolog Deleted On Chromosom...mentioning
confidence: 99%
“…Somatic PTEN mutations, combined with KRAS mutations, may predispose to invasive and metastatic endometrioid ovarian cancer. Targeted therapies for these mutations in ovarian cancer type I have been unsatisfactory [82,83]. Ovarian cancer risk-reducing surgery is not recommended for PTEN pathogenic variant carriers, but they face an increased risk of endometrial cancer (approximately 5-10%) [76].…”
Section: Pten-the Phosphatase and Tensin Homolog Deleted On Chromosom...mentioning
confidence: 99%
“…In the ovarian cell line, overexpression of PTEN promoted ageing by promoting p21 expression. Ke et al (2021) showed that PTEN increased TRIM39 expression, which binds to p21 and inhibits p21 degradation [65]. In human lung adenocarcinoma A549 cells, siPTEN accelerated bleomycin-induced premature senescence by increasing the expression of the p16, p21 protein and increasing SA-β-gal activity.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Cell senescence could affect the promotion of cell-autonomous reprogramming of non-stem cancer cells into cancer stem cells [129,125]. The important mediators of senescenceinduced cell reprogramming are the transcription factors Oct4, Sox2, Klf4, c-Myc (OSKM), and IL-6, while expression could depend on the absence of loci INK4a and p53 [65,[129][130][131].…”
Section: Two Faces Of Cancer Cell Senescence Positive and Negative As...mentioning
confidence: 99%
“…It is involved in and regulates various activities and signal transduction processes in cancer development ( 8 ). Naringin is commonly used as a phosphatase and tensin homolog agonist to interfere with the biological action of OC cells ( 9 ). In animal experiments, naringin inhibits tumor growth ( 10 ).…”
Section: Introductionmentioning
confidence: 99%